2008
DOI: 10.1128/jcm.00944-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Selective Chromogenic (chromID VRE) and Bile Esculin Agars for Isolation and Identification of vanB -Containing Vancomycin-Resistant Enterococci from Feces and Rectal Swabs

Abstract: The new chromogenic agar chromID VRE (cIDVRE; bioMérieux) was compared with bile esculin agar (BD) containing 6 mg/liter vancomycin for the detection of colonization with vanB-containing vancomycin-resistant enterococci (VRE). At 48 h of incubation, the results obtained with both media were comparable. However, cIDVRE detected significantly more VRE at 24 h (39.3% versus 21.3%, P ‫؍‬ 0.003), and its use may facilitate the timely implementation of infection control procedures.Vancomycin-resistant enterococci (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Preliminary findings direct to a similar trend in other European countries like Sweden (Soderblom et al, 2010;Fang et al, 2010). If this increased VanB-type prevalence is linked to a supposed reservoir of vanB among enterococcal or non-enterococcal intestinal colonizers (Stamper et al, 2007;Young et al, 2007;Graham et al, 2008;Usacheva et al, 2010;Bourdon et al, 2010;Werner et al, 2011c) or simply linked to an improved and better identification of low-level expressed VanB-type resistance (Pendle et al, 2008;Grabsch et al, 2008a;Grabsch et al, 2008b;Stamper et al, 2010) in relation to a reduced breakpoint as defined by EUCAST (EUCAST Clinical Breakpoint Table v. 1.1 2010-04-27) 6 remains to be elucidated in further studies.…”
Section: Europementioning
confidence: 60%
See 1 more Smart Citation
“…Preliminary findings direct to a similar trend in other European countries like Sweden (Soderblom et al, 2010;Fang et al, 2010). If this increased VanB-type prevalence is linked to a supposed reservoir of vanB among enterococcal or non-enterococcal intestinal colonizers (Stamper et al, 2007;Young et al, 2007;Graham et al, 2008;Usacheva et al, 2010;Bourdon et al, 2010;Werner et al, 2011c) or simply linked to an improved and better identification of low-level expressed VanB-type resistance (Pendle et al, 2008;Grabsch et al, 2008a;Grabsch et al, 2008b;Stamper et al, 2010) in relation to a reduced breakpoint as defined by EUCAST (EUCAST Clinical Breakpoint Table v. 1.1 2010-04-27) 6 remains to be elucidated in further studies.…”
Section: Europementioning
confidence: 60%
“…The reason(s) for this remain unknown and are not linked to a supposed larger reservoir of the vanB cluster in commensal intestinal colonizers (Padiglione et al, 2000), rates of which were similar in Australian, US-American and European studies (Stamper et al, 2007;Graham et al, 2008;Grabsch et al, 2008b;Bourdon et al, 2010;Werner et al, 2011c). A larger reservoir of vanB-type resistance in isolates from commercial animal farming associated with an avoparcin use is unlikely; avoparcin use was ceased in Australia in 2000 and Singapore has no significant agriculture at all thus excluding a distinct animal vanB-type VRE reservoir (see chapter 7).…”
Section: Asia Australia and New Zealandmentioning
confidence: 95%
“…All studies reported similar rates of recovery of both VRENFM and VRENFS from chromogenic agars to those from BEAV (1,2,(4)(5)(6)(7)10). CVRE appeared to perform better than the other chromogenic agars compared to BEAV, but a direct comparison is needed to provide the most accurate comparison.…”
mentioning
confidence: 89%
“…Confirmation of VRE using this medium requires 48 to 72 h. Chromogenic agars to detect VRE demonstrate promise (1)(2)(3)(4)(5)(6)(7)10). BBL CHROMagar VanRE (CVRE; BD Diagnostics, Sparks, MD) is a selective and differential chromogenic agar under development for the detection of vancomycin-resistant E. faecium (VRENFM) and vancomycin-resistant Enterococcus faecalis (VRENFS).…”
mentioning
confidence: 99%
“…The most common specimens to screen for colonization with VRE are rectal swabs or stool specimens. Several selective and differential media have been developed and evaluated specifically for the purpose of screening for VRE (2)(3)(4)(5)(6)(7)(8)10). Campylobacter (Campy) agar, which supports the growth of VRE and contains 10 g/ml vancomycin, is readily available in most clinical laboratories due to its use in the plating of routine stool cultures to isolate Campylobacter jejuni.…”
mentioning
confidence: 99%